On the licensing of PP complements - Castillo, Concha (Estudios Ingleses de la Universidad Complutense, 2005)
This paper deals with the hypothesis that PP complements are licensed through a PrepTrP projection that is located in between vP and VP and that is in charge of checking the Case features of PP complements, in a similar fashion to DP complements. The transitivity projection PrepTrP is instantiated in active structures but not in passive structures, with the result that Case-checking applies in the former, but not in the latter. This explains (i) why full PPs are not passivisable, the only possibility being preposition stranding, and (ii) why VP-adverbs cannot be placed in between V and P in passive structures. The abovementioned aspects are accounted for without resorting to reanalysis. Finally, an argument that is standardly used to deny the Case properties of PP complements is viewed from a different perspective: namely, the possibility of placing VP-adverbs in between V and the PP complement itself in active structures is explained here through the covert movement of the features of PP.